2017
DOI: 10.1063/1.4976198
|View full text |Cite
|
Sign up to set email alerts
|

In/GaN(0001)-(3×3)R30° adsorbate structure as a template for embedded (In, Ga)N/GaN monolayers and short-period superlattices

Abstract: We explore an alternative way to fabricate (In,Ga)N/GaN short-period superlattices on GaN(0001) by plasmaassisted molecular beam epitaxy. We exploit the existence of an In adsorbate structure manifesting itself by a ( √ 3 × √ 3)R30 • surface reconstruction observed in-situ by reflection high-energy electron diffraction. This In adlayer accommodates a maximum of 1/3 monolayer of In on the GaN surface and, under suitable conditions, can be embedded into GaN to form an In 0.33 Ga 0.67 N quantum sheet whose width … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…In fact, MBE growth of high-quality, ultrathin GaN (as well as InN) QWs has been demonstrated frequently. [18][19][20][21][22][23] However, MOVPE growth is quite rare, [16,22] despite its technological importance. In this study, we demonstrate self-limiting of the GaN thickness to the ML scale during MOVPE growth, facilitating the fabrication of highly reproducible ultrathin GaN QWs.…”
Section: Self-limiting Growth Of Ultrathin Gan/aln Quantum Wells For mentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, MBE growth of high-quality, ultrathin GaN (as well as InN) QWs has been demonstrated frequently. [18][19][20][21][22][23] However, MOVPE growth is quite rare, [16,22] despite its technological importance. In this study, we demonstrate self-limiting of the GaN thickness to the ML scale during MOVPE growth, facilitating the fabrication of highly reproducible ultrathin GaN QWs.…”
Section: Self-limiting Growth Of Ultrathin Gan/aln Quantum Wells For mentioning
confidence: 99%
“…To fabricate such ultrathin GaN QWs embedded in Al(Ga)N, molecular beam epitaxy (MBE) appears to be better suited than metalorganic vapor phase epitaxy (MOVPE) because MBE can precisely control the thickness with the assistance of a reflection high‐energy electron diffraction technique. In fact, MBE growth of high‐quality, ultrathin GaN (as well as InN) QWs has been demonstrated frequently . However, MOVPE growth is quite rare, despite its technological importance.…”
mentioning
confidence: 99%
“…A series of four SL samples each consisting of ten periods of polar InGaN QWs separated by GaN barriers of different thickness were grown by molecular beam epitaxy (MBE) at 550 °C 23 . Composition and thickness of the InGaN layers and the GaN barriers are quantified by TEM throughout the entire sample series.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, we have observed experimentally a strong decrease of the emission intensity for the 6 MLs thick barrier sample in PL measurements for different excitation and detection conditions. Thus, reducing the hole localization enhances their probability of reaching non-radiative recombination centers in the GaN barriers 23 . Since the GaN barriers were grown at 550 °C, optimized for achieving high In contents in the QWs, it is far below the optimum for GaN and, thus, results in a high number of point defects.…”
Section: Discussionmentioning
confidence: 99%
“…MOCVD studies of InN have largely focused on the growth of nanostructures such as quantum dots or dashes (QDs) due in part to the natural formation of these structures under large lattice mismatch conditions. Studies via molecular beam epitaxy (MBE) have shown evidence for stress driven surface reconstructions resulting in the formation of In 0.33 Ga 0.67 N instead of pure InN quantum wells in (0001) InN/GaN multi-layer structures (Suski et al, 2014;Chèze et al, 2017). Some MBE studies report monolayer-thick strained InN layers and, while these layers are useful for digital alloy applications (Yoshikawa et al, 2007;Yoshikawa et al, 2008;Gorczyca et al, 2018), they have limited usage in infrared optoelectronics, as their very thin nature typically leads to a blue shift resulting in emission in the visible range of the electromagnetic spectrum (Wu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%